Conhecimento científico e relações pedagógicas: instrumento de trabalho do professor - Pfeffer, Ivanir Maria (2013)
This research is about the scientific knowledge (science), which is identified as instrument of the teacher's work. Firstly the study followed the reflection s coming from students approved by some members of Class Council, who belong to the “Colégio Estadual Wilson Joffre – Ensino Fundamental, Médio, Normal e Profissional”, which was developed in the “Programa de Desenvolvimento Educacional”. This way, by cont inuing the study it was understood that the Class Council constitutes a stage of a process involving scientific knowledge expressed in the teacher's work, in the relationship between teacher and student, between the processes of teaching and learning. The n , we realized that the goal of the study was to investigate the scientific knowledge while teacher’s work instrument. So, it was necessary to understand how the knowledge is processed in humans as well, reconsider the work of those involved in this process over space and school time, and elucidate the reasons behind the fact that for so many students the acquisition of knowledge transmitted by teachers does not get to that proposed. In order to develop the problem it was necessary to use the theoretical res earch in primary and secondary sources. It was concluded that school, teacher, student and knowledge result in concrete and imbricate situations the system of production and in the class antagonisms, which makes that teacher teach that student appropriates knowledge, and which embraces knowledge as a social good that should be available in terms of quality and equality for all and emphasized the work with knowledge in a dialectical logic that allows it demonstrate, understand and deal with the reality in di fferent dimensions.